Unconstraining Methods in Revenue Management Systems: Research Overview and Prospects. (10th July 2012) - Guo, Peng; Xiao, Baichun; Li, Jun
Abstract : Demand unconstraining is one of the key techniques to the success of revenue management systems. This paper surveys the history of research on unconstraining methods and reviews over 130 references including the latest research works in the area. We discuss the relationship between censored data unconstraining and forecasting and review five alternative unconstraining approaches. These methods consider data unconstraining in various situations such as single-class, multi-class, and multi-flight. The paper also proposes some future research questions to bridge the gap between theory and applications.